Initial/Final Tone Agreement in Ekegusii (Bantu; Kenya) - Larry M. Hyman (Anuario del Seminario de Filología Vasca "Julio de Urquijo")
In this paper I present an unusual Bantu tonal phenomenon where certain “cells” in the verb paradigm require a tonal agreement between the first syllable (the subject prefix) and the last syllable (an inflectional ending). Such a long-distance dependency raises the question of whether it is tone alone that can do this. I first provide an overview of the phenomenon in Ekegusii (Kenya), and then show that a relative construction in geographically and genetically distant Grassfields Bantu languages of Cameroon can help us understand both the nature and history of the more evolved situation seen in Ekegusii. I conclude that although initially surprising, initial/final tone agreement has a natural diachronic source and is not so crazy—even from a synchronic point of view.